Saccharomyces boulardii Stimulates Intestinal Immunoglobulin A Immune Response to Clostridium difficile Toxin A in Mice - Qamar, Amir (American Society for Microbiology, 2001)
Saccharomyces boulardii is a nonpathogenic yeast that protects against antibiotic-associated diarrhea and recurrent Clostridium difficile colitis. The administration of C. difficile toxoid A by gavage to S. boulardii-fed BALB/c mice caused a 1.8-fold increase in total small intestinal immunoglobulin A levels (P = 0.003) and a 4.4-fold increase in specific intestinal anti-toxin A levels (P < 0.001). Enhancing host intestinal immune responses may be an important mechanism for S. boulardii-mediated protection against diarrheal illnesses.